Studi Living Hadis: Pembentukan Karakter Muslim Anak Usia Dini di Yayasan Ummah - Azzahra, Annisa Fitri; Hakim, Luqmanul; Wendry, Novizal (Prodi Ilmu Hadis Fakultas Ushuluddin dan Dakwah Institut Agama Islam Negeri Madura, 2024)
This study aims to analyze how the Prophet’s hadith contribute to the character development of Muslim children at the Ummah Islamic Learning Center Foundation. This research employs a field research method with a phenomenological approach, utilizing direct observation and semi-structured interviews with teachers and students. Data were analyzed qualitatively to understand the real-life implementation of hadith in daily character-building activities. The study focuses on three hadith: the prohibition of anger, the recommendation to smile, and the prohibition of eating and drinking while standing. Based on hadith authentication, two hadith are categorized as ṣaḥīḥ and one as ḥasan. The findings indicate that the teaching of these hadith is not merely theoretical but significantly influences children’s behavior, fostering positive character traits in both personal and social contexts. This research highlights the importance of incorporating hadith-based character education in early childhood Islamic education and suggests that similar methods could be applied in other Islamic learning institutions.